2019
DOI: 10.1097/rti.0000000000000434
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Outpouchings

Abstract: Cardiac outpouchings pose a diagnostic challenge when encountered in practice, as the signs, symptoms, and initial investigations, such as radiographs and electrocardiogram, are nonspecific. They may remain asymptomatic and be incidentally detected. However, a few may present with progressive shortness of breath, thromboembolic complications, arrhythmias, pressure effects, rupture, or even death. Imaging is of paramount importance in establishing an accurate diagnosis, delineating morphology and extent of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Diverticula. Cardiac diverticula are described as congenital outpouchings which contain all three layers of cardiac wall (endocardium, myocardium, and pericardium) and display a synchronous contractility with the corresponding cardiac chamber, as compared to aneurysms and pseudoaneurysms (which are akinetic or dyskinetic outpouchings) [1,28]. Although no recent reports have been explained, the current epidemiology of cardiac diverticula and early studies showed a prevalence rate of 0.4% among 750 cardiac necropsy cases, while one analysis by multidetector computed tomography reported an increased prevalence to 2.2% [44].…”
Section: Cardiacmentioning
confidence: 99%
See 3 more Smart Citations
“…Diverticula. Cardiac diverticula are described as congenital outpouchings which contain all three layers of cardiac wall (endocardium, myocardium, and pericardium) and display a synchronous contractility with the corresponding cardiac chamber, as compared to aneurysms and pseudoaneurysms (which are akinetic or dyskinetic outpouchings) [1,28]. Although no recent reports have been explained, the current epidemiology of cardiac diverticula and early studies showed a prevalence rate of 0.4% among 750 cardiac necropsy cases, while one analysis by multidetector computed tomography reported an increased prevalence to 2.2% [44].…”
Section: Cardiacmentioning
confidence: 99%
“…ey are commonly located in the anterosuperior wall and have generally a broad neck and a smooth surface. Atrial diverticula should not be confounded with accessory atrial appendages, which are mostly located in the lateral and inferior walls (along the line of fusion between pulmonary veins and the embryonic atrial chamber), usually present a narrow neck and an irregular surface, due to the presence of pectinate muscles [1]. Cardiac diverticula are often asymptomatic and can be incidentally detected by imaging techniques.…”
Section: Cardiacmentioning
confidence: 99%
See 2 more Smart Citations